Peran Strategis Kepala Madrasah dalam Membangun Kemitraan dengan Masyarakat untuk Peningkatan Kualitas Pendidikan - Aniati, Ana (INCARE, International Journal of Educational Resources, 2025)
Improving the quality of education in Islamic schools (madrasahs) depends not only on internal institutional factors but also on the principal’s strategic ability to build partnerships with the community. This study aims to explore the strategic role of the school principal in fostering community partnerships to improve educational quality at MTs Wringinrejo, Banyuwangi. This research employs a descriptive qualitative approach using in-depth interviews with the principal, teachers, community leaders, parents, and alumni. The findings reveal that the principal demonstrates an active transformational leadership style in developing social networks through extracurricular programs, infrastructure support, student organization engagement, and alumni empowerment. These efforts have led to an increase in student enrollment and broader community involvement in school development. This study contributes to the understanding of the importance of participatory leadership in community-based Islamic education.